Investigation of friction coefficients of veneers as a function of fibre direction and moisture content : Istraživanje faktora trenja između furnira kao funkcije smjera protezanja vlakanaca i sadržaja vode - Buchelt, Beate (Array, 2019)
During the manufacture of veneer based moulded parts, veneers move against one another. Friction is caused due to this movement. Different conditions, such as gluing or fibre direction, could influence the friction coefficients and thus the moulding process. For a better understanding of the manufacturing process of veneer based moulded parts, it is important to know which parameters influence friction and friction coefficients. In this paper, results of friction investigations are presented. Thereby the moisture content of the used veneers was varied as well as the fibre direction. Considering the manufacture conditions, the investigations were also conducted with glue-coated veneers. The results prove an influence of fibre direction but this influence depends on moisture content.